Differential clinical features of patients with clinically amyopathic dermatomyositis who have circulating anti-MDA5 autoantibodies with or without myositis-associated autoantibodies. (July 2018) - Yamaguchi, Koichi; Yamaguchi, Aya; Kashiwagi, Chiharu; Sawada, Yuri; Taguchi, Kohei; Umetsu, Kazue; Oshima, Kazuma; Uchida, Megumi; Suzuki, Masafumi; Kono, Shunichi; Takemura, Masao; Masubuchi, Hiroaki; et al.
Abstract: Background: Anti-melanoma differentiation-associated gene 5 (MDA5) autoantibodies have been identified as myositis-specific autoantibodies that are often associated with clinically amyopathic dermatomyositis (CADM) and a poor prognosis due to rapidly progressive interstitial lung disease (RP-ILD) in East Asian patients. Besides anti-MDA5 autoantibodies, patients with CADM may have myositis-associated autoantibodies (MAAs), which characterize other connective tissue diseases such as rheumatoid arthritis and Sjögren's syndrome. However, the clinical significance of the coexistence of anti-MDA5 autoantibodies and MAAs in patients with CADM remains unclear. Methods: We retrospectively analyzed 24 patients with CADM who had anti-MDA5 autoantibodies. Their clinical phenotypes including laboratory test results, high-resolution lung computed tomography data, response to therapy, and prognosis were compared between those who were positive and negative for MAAs, such as antinuclear antibody (ANA), anti-cyclic citrullinated peptide (CCP), anti-SSA, and anti-SSB antibodies. Results: Among 24 patients, 9 (37.5%) additionally had at least one of the MAAs examined in this study: 1 patient was positive for ANA, 5 for anti-CCP, 5 for either anti-SSA or anti-SSB, 1 for anti-cardiolipin, and 1 for anti-Scl-70. Although all anti-MDA5-positive patients with CADM had ILD, the MAA-positive patients showed a lower risk of developing RP-ILD (p = 0.03), a more favorable response to combination therapy of corticosteroids and immunosuppressive agents, and a lower mortality rate than patients with no MAAs (p = 0.03). Conclusions: Our data suggest that anti-MDA5-positive patients with CADM who also have MAAs have a better prognosis than those without MAAs; thus, anti-MDA5 autoantibodies by themselves may not be strong predictors of worse clinical outcomes in patients with CADM. Coexistent MAAs could be biomarkers for a favorable prognosis in anti-MDA5-positive patients with CADM. Highlights: MAA-positive patients had a lower risk of developing RP-ILD. Immunosuppressive treatment was effective for MAA-positive patients with RP-ILD. MAAs may serve as a favorable prognostic marker for MDA5-positive CADM patients.